Impact of a kidney-adjusted ERAS® protocol on postoperative outcomes in patients undergoing partial nephrectomy - Walach, Margarete; Körner, Mona; Weiß, Christel; Terboven, Tom; Mühlbauer, Julia; Wessels, Frederik; Worst, Thomas; Kowalewski, Karl-Friedrich; Kriegmair, Maximilian (Langenbeck's archives of surgery, 2024)
Purpose Evaluation of a kidney-adjusted enhanced recovery after surgery (ERAS®) protocol (kERAS) in patients undergoing nephron-sparing surgery (PN). Methods The kERAS protocol is a multidimensional protocol focusing on optimized perioperative fluid and nutrition management as well as strict intraoperative and postoperative blood pressure limits. It was applied in a prospective cohort (n = 147) of patients undergoing open or robotic PN. Patients were analyzed for the development of acute postoperative renal failure (AKI), achievement of TRIFECTA criteria, upstaging or new onset of chronic kidney disease (CKD) and length of hospital stay (LOS) and compared to a retrospective cohort (n = 162) without application of the protocol. Results Cox regression analyses could not confirm a protective effect of kERAS on the development of AKI post-surgery. A positive effect was observed on TRIFECTA achievement (OR 2.2, 95% CI 1.0-4.5, p = 0.0374). Patients treated with the kERAS protocol showed less long-term CKD upstaging compared to those treated with the standard protocol (p = 0.0033). There was no significant effect on LOS and new onset of CKD. Conclusion The implementation of a kERAS protocol can have a positive influence on long-term renal function in patients undergoing PN. It can be used safely without promoting AKI. Furthermore, it can be realized with a manageable amount of additional effort.
Gesehen am 24.03.2025